The Effect of Clean Energy Technology Infrastructure Development on Regional Economic Growth in Indonesia - Judijanto, Loso; Ilham, Ilham; Vandika, Arnes Yuli (Westscience Press, 2024)
This study investigates the effect of clean energy technology infrastructure development on regional economic growth in Indonesia. Using a quantitative research design, data were collected from 70 respondents across different regions using a Likert scale ranging from 1 to 5. The analysis was conducted using SPSS version 26 to examine the relationship between clean energy infrastructure and regional economic performance. The results show a strong positive correlation between clean energy technology infrastructure and regional economic growth, with a statistically significant relationship. Furthermore, multiple regression analysis indicates that clean energy infrastructure development significantly predicts economic growth, while geographic location and government policy also play important roles. These findings suggest that investments in clean energy infrastructure are crucial drivers of regional economic development and highlight the need for supportive policies to maximize the benefits of renewable energy projects. This study provides valuable insights for policymakers and stakeholders in advancing sustainable development through clean energy initiatives.